Analisis Komparatif Ijarah dan Leasing dalam Perspektif Fiqhi Muamalah - Kamil, Muh Ahsan (Journal of Islamic Economic Studies, 2025)
Ijarah contracts and leasing contracts are two things that are often equated by the community because both refer to the same function, namely leasing. This study aims to compare ijarah contracts with leasing from the point of view of muamalah fiqhi to see the differences between the two and discuss the law of both. The method used is comparative qualitative using secondary data obtained by library research techniques. The results of this study are that although they have similarities, ijarah and leasing also have different characteristics and practices between ijarah and leasing which lie in their object, method of payment, transfer of ownership, and the practice of lease purchase and sale and lease back. So that from the muamalah fiqhi aspect, there are restrictions relating to leasing such as usury, gharar, and the prohibition of bai al-inah. Leasing practices can be permissible on the condition that they must leave practices that are prohibited in Islam.